Regulation of food intake by neuropeptide Y in goldfish - Narnaware, Yuwaraj; Peyon, Pierre P.; Lin, Xinwei; Peter, Richard E. (My University, 2000)
In mammals, neuropeptide Y (NPY) is a potent orexigenic factor. In the present study, third brain ventricle (intracerebroventricular) injection of goldfish NPY (gNPY) caused a dose-dependent increase in food intake in goldfish, and intracerebroventricular administration of NPY Y1-receptor antagonist BIBP-3226 decreased food intake; the actions of gNPY were blocked by simultaneous injection of BIBP-3226. Goldfish maintained on a daily scheduled feeding regimen display an increase in NPY mRNA levels in the telencephalon-preoptic area and hypothalamus shortly before feeding; however, a decrease occured in optic tectum-thalamus. In both fed and unfed fish, brain NPY mRNA levels decreased after scheduled feeding. Restriction in daily food ration intake for 1 wk or food deprivation for 72 h resulted in increased brain NPY mRNA levels. Results from these studies demonstrate that NPY is a physiological brain signal involved in feeding behavior in goldfish, mediating its effects, at least in part, through Y1-like receptors in the brain.
Keywords: feeding; gene expression; growth hormone; brain